Utility Sector Performance Post Reforms: Investigating the South Asian Economies. Issue 2 (1st June 2014) - Vu, Khoung M.; Gurtoo, Anjula
<x xml:space="preserve">Abstract</x> This article critically evaluates the utility sector performance of South Asian economies for the last two decades. Utility sector inputs are key to socioeconomic development, contributing to poverty reduction by fueling economic growth and enabling the fulfillment of basic human needs. After two decades of utility sector reforms, is the sector contributing significantly to the economic growth of the East Asian nations? And what does this augur for the poor? To answer these questions, the results for the five South Asian economies are put side by side, namely, India, Bangladesh, Nepal, Pakistan, and Sri Lanka, focused on the period from 1990 to 2008. Results show a declining GDP share of the sector for countries such as India, Bangladesh, and Pakistan. Put alongside the sector's employment share, the decline in the GDP share along with growth in the employment share for India, Bangladesh, and Pakistan indicate the lack of sectoral expansion as well as modernization. Moreover, a declining contribution of the utility sector to the overall growth of the nation, as compared to other sectors, is evident for all the countries except Sri Lanka. We discuss these and other results in light of the impact on the socially and economically marginalized populations of these countries.